2012
DOI: 10.5381/jot.2012.11.1.a7
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Look at ALIA4J.

Abstract: New programming languages supporting advanced modularization mechanisms are often implemented as transformations to the imperative intermediate representation of an already established language. But while their core constructs largely overlap in semantics, re-using the corresponding transformations requires re-using their syntax as well; this is limiting. In the ALIA4J approach, we identified dispatching as fundamental to most modularization mechanisms and provide a meta-model of dispatching as a rich, extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…In our prior work [5], we classified AOP as one kind of advanceddispatching (AD) languages and we have shown that AO concepts can be perfectly matched to the AD domain. Our work is carried out based on a framework for executing AD programs.…”
Section: Design Proposalsmentioning
confidence: 97%
“…In our prior work [5], we classified AOP as one kind of advanceddispatching (AD) languages and we have shown that AO concepts can be perfectly matched to the AD domain. Our work is carried out based on a framework for executing AD programs.…”
Section: Design Proposalsmentioning
confidence: 97%
“…Our current implementation of the debugger is based on the ALIA4J NOIRIn execution environment [10], which is implemented as a Java 6 agent intercepting the execution of the base program to perform the dispatch. NOIRIn can integrate with any standard Java 6 JVM, therefore our approach does not require using a custom virtual machine.…”
Section: A Fine-grained Customizable Debugger For Advanced-dispatchimentioning
confidence: 99%
“…In this work, we use join point instead, because join points are modelled as firstclass objects in our execution environment NOIRIn [10]. Besides, we want to distinguish our work from existing trace-based debuggers.…”
Section: Back-end Design and Implementationmentioning
confidence: 99%
See 2 more Smart Citations